Kajian Hukum terhadap Pengelolaan Sumber Daya Alam Berbasis Limbah Pasar untuk Pembuatan Pupuk Kompos - Samariadi Samariadi; Desi Marta Shelvyani; Safarudin Safarudin; Dwi Agustin; Dela Shelya Febrina; Elmi Yanti; Dian Putri Intana; Dinda Syafita; Dina April; Eksaudia Azumi Kezia; Mizi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This journal looks at the legal concerns of managing natural resources by producing compost using a market-based method based on garbage. This study's primary goal is to evaluate the efficacy and compliance of the legal requirements controlling the use of market trash as a raw material for compost fertilizer. The study's findings indicate that there are several pertinent laws that offer a legal framework for market waste management, including the Environmental Law and government waste management rules. However, there are obstacles to the law's implementation and enforcement, such as a lack of knowledge among business actors and oversight flaws. To ensure sustainability and efficiency in managing market waste as a resource for making compost, this study also found that, despite the existence of existing regulations, regulatory updates and harmonization are still required. To maximize the environmental and economic benefits of market waste management, this research recommends improvements in regulations and law enforcement, as well as increased education and training for business actors.The results of the study indicate that the utilization of market waste for making compost has great potential in supporting organic farming and reducing the volume of waste that ends up in landfills. However, the implementation of this program requires a deep understanding of applicable regulations, as well as support from the government and the community. This article concludes that comprehensive legal-based waste management can improve the efficiency and sustainability of natural resource management, as well as have a positive impact on community welfare.